1998
DOI: 10.1007/s004210050452
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocytes participate significantly in blood transport of amino acids during the post absorptive state in normal humans

Abstract: To investigate the participation of erythrocytes in the blood transport of amino acids during the course of intestinal absorption in humans, erythrocyte and plasma amino-acid concentrations were determined following ingestion of an oral load of amino acids. In addition to baseline plasma and erythrocyte amino acid concentrations in 18 subjects, plasma and erythrocyte amino acids kinetics during the 125 min following an oral amino acid load were further determined in 9 of the 18 subjects. The results showed tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 23 publications
2
15
0
Order By: Relevance
“…Arginine translocation through RBC membranes is carrier-mediated with simple Michaelis-Menten kinetics, with a high affinity, but with low capacity for transporting the amino acid [40]. Indeed, for some amino acids, erythrocyte transport sometimes exceed that of serum and significant correlation coefficients show that strong serum-erythrocyte relationships exist for arginine and ornithine [41]. Therefore, both serum and RBC are physiologically involved in the blood transport of amino acids in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Arginine translocation through RBC membranes is carrier-mediated with simple Michaelis-Menten kinetics, with a high affinity, but with low capacity for transporting the amino acid [40]. Indeed, for some amino acids, erythrocyte transport sometimes exceed that of serum and significant correlation coefficients show that strong serum-erythrocyte relationships exist for arginine and ornithine [41]. Therefore, both serum and RBC are physiologically involved in the blood transport of amino acids in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Amino acid levels in human plasma and erythrocytes were found to increase significantly in the post-absorptive state following an oral loading of amino acids (Agli et al 1998). A separate study in a human exercise challenge demonstrated that erythrocytes increased their carrying capacity of amino acids during exercise with no corresponding change in the plasma levels (MacLaren et al 2000).…”
Section: Introductionmentioning
confidence: 94%
“…The presence of facilitated diffusion and secondary active transport systems would generate a capacity for the erythrocyte to accumulate amino acids at concentrations different to those observed in the plasma. It was shown that erythrocytes and plasma have very different profile characteristics where at least eight amino acids were measured at significantly higher levels in the erythrocytes than the corresponding plasma and two amino acids (glutamine and arginine) were found to be lower (p < 0.01) (Agli et al 1998). Aspartic acid showed contrasting levels in erythrocytes and plasma analysed from resting blood samples, with 451-484 µM in the erythrocytes compared with 14.5-15.1 µM in the corresponding plasma (MacLaren et al 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, RBC are independent of mitochondrial energy supply. Rather, BCAA and other amino acids are actively transported by RBC through blood stream and, moreover, RBC actively participate in blood tissue amino acid exchange explaining the observed positive associations for BCAA and their catabolites as well as for some other amino acids, for example, lysine and ornithine. Considering the role of BCAA as metabolic marker in health and disease, it has to be noted that increased levels of circulating BCAA are typically associated with insulin resistance (IR), while the positive association between haematologic parameters RBC, HGB and HCT with IR is also well documented .…”
Section: Discussionmentioning
confidence: 99%